Improving Student Internalization of Disaster Knowledge by Participating in Learning Package Development - Rina Suryani Oktari; Intan Dewi Kumala (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2020)
In the subject of disaster education, it is crucial to establish a practical approach to give an impactful impression for the student so that it can increase self-awareness as well as for it to be applicable in daily life and memorized longer in each individual. This community services program titled